Arterial tortuosity syndrome in a neonate - Indu Khosla; Tanushri Mukherjee (Wolters Kluwer Medknow Publications, 2018)
Background : Arterial Tortuosity Syndrome (ATS) is a rare, autosomal recessive connective tissue disorder characterized by elongated and tortuous large and medium-sized arteries involving aorta and pulmonary arteries along with dysmorphic facial features, skin and joint laxity and hernia formation. We present here one case of ATS.